The risks of operations with derivative financial instruments as a threat to the financial stability of commercial banks - O.V.; A.O. (Економіка, управління та адміністрування)
The article discusses the risks of the operations of commercial banks with derivative financial instruments. The emergence of new types of derivatives for the Ukrainian financial market in recent years, the establishment of provisions on defining their essence, classification and regulation in the regulatory framework, as well as the strategy of the financial sector for the development of the derivatives market, indicate the need to identify the threats that these instruments carry. It was established that the aggregate risk is formed from the following components: risks of derivatives as objects of operations of commercial banks, among which the key types are credit, market, liquidity and operational risks; as well as systemic risk, which is formed as a result of macroeconomic shock events, imbalances or the spread of negative phenomena. The identification of the above-mentioned risks made it possible to determine ways of reducing their impact on the activities of commercial banks during operations with derivatives. It was determined that if the negative impact of the bank’s individual risks can be reduced with the help of effective methods of the internal risk management system, then the systemic risk requires increased attention of regulators, since its management is complicated by such characteristics as the random occurrence, unpredictability, disruption of the functioning of the financial system, large-scale (systemic) impact, impact on the real sector of the economy, significant risk of default, connection between various elements of the financial system. It was found that certain operations of commercial banks with derivatives, as well as the derivatives market itself, can turn into an accelerator of systemic risk, the implementation of which will lead not only to a decrease in the financial stability of an individual institution, but also to the bankruptcy of other participants and a banking crisis, which will have negative consequences for financial security and the real sector of the economy. Therefore, commercial banks should maintain a sufficient level of financial stability and comply with the prudential requirements of the regulator regarding standards and restrictions to increase the ability to withstand the negative consequences of external unpredictable threats and in periods of economic instability.